An Analysis On Students’ Ability in Using Simple Present Tense at VII Grade of SMP Negeri 15 Sijunjung on Academic Year 2022/2023 - Amelia Rinanda; Dewi Yupita Sinaga; Fitri Susanti (Jurnal Pendidikan Tuntas, 2023)
This research is purposed to know students’ ability and the level of their ability of VII grade of SMP Negeri 15 Sijunjung in using simple present tense. This research is categorized as descriptive analysis, because this research the focus on the students’ ability in using simple present tense. The respondent of the research is 32 of VII grade of SMP Negeri 15 Sijunjung. An analysis of the test is to know what extent was the students’ ability level in using simple present tense, and did the students’ ability in using simple present tense. The result of the test was analyzed to know the students’ ability in using the simple present tense. The finding of this research shows that the average score in the form of the simple present of verb be is 33,89%, and the average score in the form of simple present tense of verb is 57,04%. In addition, the result of the test shows that the students’ ability in using simple present tense is on low level. from the data got it showed that the students did errors most is in the usage of simple present tense is simple present tense of verb be. The students’ ability in using simple present tense is still low. Keywords: Students’ Ability, Simple Present Tense, Descriptive Analysis